2007
DOI: 10.1063/1.2731786
|View full text |Cite
|
Sign up to set email alerts
|

Effective interaction parameter of linear/star polymer blends and comparison with that of linear/linear and star/star blends

Abstract: The authors present a detailed study of the microscopic parameters, which control the miscibility in binary linear/star polymer blends. The effective interactions of linear/star polymer blends are studied by means of Monte Carlo simulations and comparison is made with linear/linear and star/star blends, which they also determined. Using the bond fluctuation model on a simple cubic lattice, the authors are able to simulate symmetric linear/linear, star/star, and, for the first time, linear/star blends with a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Equation ( 7) means that a pair of monomers (A, B) is defined to have a pairwise contact if their distance is less than r n . Similar quantities have been also used to characterize the incompatibility between linear and star chains in polymer melts and blends [76][77][78]. As can be seen from figure 4, the number of contacts A-B averaged over all conformations increases as the number of blocks n increases.…”
Section: Resultsmentioning
confidence: 99%
“…Equation ( 7) means that a pair of monomers (A, B) is defined to have a pairwise contact if their distance is less than r n . Similar quantities have been also used to characterize the incompatibility between linear and star chains in polymer melts and blends [76][77][78]. As can be seen from figure 4, the number of contacts A-B averaged over all conformations increases as the number of blocks n increases.…”
Section: Resultsmentioning
confidence: 99%
“…This interfacial tension difference can be attributed to the sterically hindered interaction of PMMA chains with the inner layer of the grafted PS brush, analogous to star-linear polymer blends. 34,35 When comparing the interactions between PMMA and end-grafted PS chains versus linear PS chains, different from star-linear polymer blends, it seems more appropriate to consider a single grafted PS chain instead of all the grafted chains on one particle together. As mentioned earlier, the composition-dependent phase separation behavior of AuPS nanoparticles is more analogous to the linear PS counterpart with the same molecular weight as one grafted chain.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with previous theoretical and experimental researches, which investigated the miscibility of star/linear binary blends based on thermodynamic interaction parameter χ eff . Theodorakis et al compared the effective interactions of linear/star, linear/linear, and star/star polymer blends by Monte Carlo simulations. They found that linear/star blends are more miscible than the corresponding linear/linear blends, and linear/star mixtures are less miscible than star/star blends.…”
Section: Resultsmentioning
confidence: 99%